Law Enforcement Against Online Gambling Advertising on Social Media: An Empirical Study of Polres Sidoarjo - Teguh R. D Putra; Azizul Hakiki (Fakultas Hukum Universitas Bhayangkara Surabaya, 2025)
The rapid expansion of digital technology has enabled online gambling operators to exploit social media platforms as primary channels for advertising illegal services, posing significant challenges to law enforcement in Indonesia. This study examines how the Sidoarjo District Police (Polres Sidoarjo) identify and respond to criminal acts involving the promotion of online gambling sites through social media, and what law enforcement measures are applied against perpetrators. Employing an empirical legal research design, primary data were gathered through semi-structured interviews with the Head of the Special Crime Sub-Unit (Kasubmit Tipiter) of Polresta Sidoarjo, supplemented by secondary data drawn from statutory instruments and academic literature. The findings indicate that Polres Sidoarjo relies primarily on cyber patrol conducted in coordination with the Cybercrime Polda Jatim to detect and flag gambling-related promotional content across major social media platforms. Enforcement, however, is constrained by a structural bifurcation of authority between the police and the Kementerian Komunikasi dan Informatika (Kominfo), limited digital forensic capacity at the local unit level, and the transnational character of illegal gambling operations. In response to these limitations, the unit has institutionalized weekly community education programs as a demand-side complement to criminal prosecution. These findings confirm and empirically specify prior scholarly conclusions regarding the persistent gap between Indonesia's legal framework on online gambling and its practical enforcement, underscoring the urgency of sustained inter-agency coordination and institutional capacity building at the local policing level.